Unmet Needs in the Treatment of RA in the Era of Jak-i: IDRA (Italian Delphi Rheumatoid Arthritis) Consensus. (9th September 2018) - Caporali, R.; Doria, A.; Ferraccioli, G. F.; Meroni, P. L.; Zavaglia, D.; Iannone, F.
Abstract : Rheumatoid arthritis is the most common autoimmune arthritis in adult population. This disease is characterized by joint damage and systemic involvement that lead to general physical and mental impairment with consequent worsening of quality of life. Rheumatoid arthritis is also associated with a large economic burden to healthcare systems. The evidence from the literature indicates that, despite available treatments, several unmet needs still interfere with rheumatoid arthritis management. Based on this evidence, some of the unmet medical needs currently present in the management of the rheumatoid arthritis were identified and a Delphi questionnaire was submitted to 60 Italian Rheumatologists. The aim of this Delphi was to achieve a broad consensus on the most relevant unmet needs identified, in order to present the Italian reality in view of the availability of new molecules that could provide an effective therapeutic option in the treatment of patients with rheumatoid arthritis.